Comparative best practices to manage corruption (Journal for Studies in Humanities and Social Sciences, 2016)
During the last two decades debates about corruption and ways to contain it have acquired a new intensity and concentrated focus. There are increasing attempts to construct a global framework of best practices to manage corruption. Because corruption is a systemic challenge that needs a long-term approach to manage, it is worthwhile focusing on best practises that have proved to be the most durable (most sustainable). Such practices that demonstrate elements of systemic reform in-clude reforms in two newly industrialised and two developed countries. In all four cases there was no masterplan and reform evolved over time. Ongoing successes reinforced the momentum of change, and these successes became institutionalised in government processes and the culture of participative governance.